RETRACTED: Formation of future specialists in the field of aquaculture and fisheries by means of vocational education - Belovitskaya Svetlana; Shatokhina Irina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001